Glossopharyngeal neuralgia associated with cardiac syncope - Burfield, Laura (BMJ Case Rep, 2016)
Glossopharyngeal neuralgia is a rare pain syndrome presenting with paroxysms of pain in the region of the glossopharyngeal nerve. Even more uncommon is the association between glossopharyngeal neuralgia and cardiac syncope. In these patients, the cardiovascular consequences may include bradycardia, hypotension and cardiac arrest. We describe the case of a 40-year-old patient who presented with this rare association of glossopharyngeal neuralgia and syncope. Multiple pauses including one lasting 14 s were noted on ambulatory ECG monitoring. In this case, the patient declined pharmacological treatment with carbamazepine or with permanent pacing and so far has been in remission from symptoms for 3 months.